2016
DOI: 10.1103/physrevb.93.085141
|View full text |Cite
|
Sign up to set email alerts
|

Reduced density-matrix functionals applied to the Hubbard dimer

Abstract: Common density-matrix functionals, the Müller and the power functional, have been benchmarked for the half-filled Hubbard dimer, which allows to model the bond dissociation problem and the transition from the weakly to the strongly correlated limit. Unbiased numerical calculations are combined with analytical results. Despite the well known successes of the Müller functional, the ground state is degenerate with a one-dimensional manifold of ferromagnetic solutions. The resulting infinite magnetic susceptibilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 54 publications
3
50
2
Order By: Relevance
“…We have however shown that the Müller functional predicts an unphysical infinite magnetic susceptibility for the half-filled Hubbard dimer [19]. It is also known to overcorrelate [55][56][57].…”
Section: The European Physical Journal Special Topicsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have however shown that the Müller functional predicts an unphysical infinite magnetic susceptibility for the half-filled Hubbard dimer [19]. It is also known to overcorrelate [55][56][57].…”
Section: The European Physical Journal Special Topicsmentioning
confidence: 99%
“…Due to the construction of the power functional by interpolation it inherits several problems from the limits [19]: We have shown that on the one hand it is missing the derivative discontinuity of the energy at integer particle numbers like the Müller functional and that it on the other hand yields an unphysical transition to an antiferromagnetic state like the Hartree-Fock approximation. The power functionals also shows a plethora of unphysical non-collinear magnetic structures and transitions.…”
Section: The European Physical Journal Special Topicsmentioning
confidence: 99%
See 3 more Smart Citations